2016
DOI: 10.1001/jamaneurol.2016.0839
|View full text |Cite
|
Sign up to set email alerts
|

Combined-Modality Therapy With Radiation and Chemotherapy for Elderly Patients With Glioblastoma in the Temozolomide Era

Abstract: IMPORTANCE The optimal management for elderly patients with glioblastoma (GBM) is controversial. Following maximal safe resection or biopsy, accepted treatment paradigms for elderly patients with GBM include combined-modality therapy (CMT) with both radiotherapy (RT) and chemotherapy (CT), RT alone, and CT alone. OBJECTIVE To evaluate the overall survival (OS) outcomes associated with RT, CT, and CMT for elderly patients with GBM in the modern temozolomide era. DESIGN, SETTING, AND PARTICIPANTS In this retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…The same variables used in the multivariate analysis were accounted for, including age, sex, CDCC score, race/ethnicity, year of diagnosis, site, T classification, N classification, facility volume, and surgical margin status. One‐to‐1 matching without replacement was completed using the nearest neighbor match on the logit of the propensity score for treatment approach with the caliper width set to 0.05 times the standard deviation of the logit of the propensity score, as previously described . Univariate cox hazard ratios (HRs) are reported.…”
Section: Methodsmentioning
confidence: 99%
“…The same variables used in the multivariate analysis were accounted for, including age, sex, CDCC score, race/ethnicity, year of diagnosis, site, T classification, N classification, facility volume, and surgical margin status. One‐to‐1 matching without replacement was completed using the nearest neighbor match on the logit of the propensity score for treatment approach with the caliper width set to 0.05 times the standard deviation of the logit of the propensity score, as previously described . Univariate cox hazard ratios (HRs) are reported.…”
Section: Methodsmentioning
confidence: 99%
“…12,22 In addition to age, patient demographic and treatment factors, including sex, race, and treatment facility type, predict the receipt of adjuvant therapy. The youngest patients in our study were significantly more likely to receive adjuvant therapy with CRT, CT, or RT than no adjuvant therapy compared with the oldest patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Elderly patients have frequently been excluded from clinical trials, 6 and those studies that do examine this population have demonstrated suboptimal survival outcomes. Chemotherapy (CT) alone, 8,9 radiotherapy (RT) alone, 10 and combined-modality therapy using CT and RT (CRT), 11,12 have all produced improved outcomes in select elderly patients. Chemotherapy (CT) alone, 8,9 radiotherapy (RT) alone, 10 and combined-modality therapy using CT and RT (CRT), 11,12 have all produced improved outcomes in select elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of 293 patients over the age of 65 showed a benefit for the combined regimen (222). A retrospective survey of the National Cancer Database yielded similar results, with combined modality treatment showing superiority over both chemotherapy alone and RT alone, in a group of 16,717 patients, with nGBM, aged 65 years or older (223). Two prospective randomized studies addressed the question of which single modality treatment would be best for elderly patients.…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 91%